Heterogeneity of HIV-1 latent reservoirs - Jia-Cong Zhao; Kai Deng; Peng Lyu; Xin Chen. (Chinese Medical Journal, 2020)
Abstract. Antiretroviral therapy (ART) can effectively inhibit human immunodeficiency virus-1 (HIV-1) replication, but is not curative due to the existence of a stable viral latent reservoir harboring replication-competent proviruses. In order to reduce or eliminate the HIV-1 latent reservoir, characteristics of the latently infected cells need to be intensively studied, and a comprehensive understanding of the heterogenous nature of the latent reservoir will be critical to develop novel therapeutic strategies. Here, we discuss the different cell types and mechanisms contributing to the complexity and heterogeneity of HIV-1 latent reservoirs, and summarize the key challenges to the development of cure strategies for acquired immunodeficiency syndrome (AIDS).